Hydrography and circulation in the Filchner Depression, Weddell Sea, Antarctica - Darelius, Elin Maria K.; Makinson, Keith; Daae, Kjersti Birkeland; Fer, Ilker; Holland, Paul R.; Nicholls, Keith W. (Journal of Geophysical Research: Oceans, 2016)
Cold and dense ice shelf water (ISW) emerging from the Filchner-Ronne Ice Shelf cavity in the southwestern Weddell Sea flows northward through the Filchner Depression to eventually descend the con- tinental slope and contribute to the formation of bottom water. New ship-born observations of hydrogra- phy and currents from Filchner Depression in January 2013 suggest that the northward flow of ISW takes place in a middepth jet along the eastern flank of the depression, thus questioning the traditional view with outflow along the western flank. This interpretation of the data is supported by results from a regional numerical model, which shows that ISW flowing northward along the eastern coast of Berkner Island turns eastward and crosses the depression to its eastern side upon reaching the Filchner ice front. The ice front represents a sudden change in the thickness of the water column and thus a potential vorticity barrier. Transport estimates of northward ISW flux based on observations ranges from 0.2 to 1.0 Sv. publishedVersion